2004
DOI: 10.4049/jimmunol.173.4.2410
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cells Specific for EBV, Cytomegalovirus, and Influenza Virus Are Activated during Primary HIV Infection

Abstract: Primary viral infections, including primary HIV infection, trigger intense activation of the immune system, with marked expansion of CD38(+)CD8(+) T cells. Whether this expansion involves only viral-specific cells or includes a degree of bystander activation remains a matter of debate. We therefore examined the activation status of EBV-, CMV-, and influenza virus (FLU)-specific CD8(+) T cells during primary HIV infection, in comparison to HIV-specific CD8(+) T cells. The activation markers CD38 and HLA-DR were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
141
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(161 citation statements)
references
References 62 publications
10
141
1
2
Order By: Relevance
“…Antigen-specific cells initially displayed an effector cell phenotype and gradually developed into YFV-17D-specific memory CD8 + T cells [10]. In contrast to other studies, no significant activation of CD8 + T cells for other viruses such as EBV could be detected [11]. In summary, YFV-17D vaccination induces a specific and protective adaptive immune response, including the generation of cytotoxic T cells, a heterogeneous TH-cell profile and potent neutralizing antibodies.…”
Section: Introductionmentioning
confidence: 65%
“…Antigen-specific cells initially displayed an effector cell phenotype and gradually developed into YFV-17D-specific memory CD8 + T cells [10]. In contrast to other studies, no significant activation of CD8 + T cells for other viruses such as EBV could be detected [11]. In summary, YFV-17D vaccination induces a specific and protective adaptive immune response, including the generation of cytotoxic T cells, a heterogeneous TH-cell profile and potent neutralizing antibodies.…”
Section: Introductionmentioning
confidence: 65%
“…This has been shown with herpesvirus infections, either due to cross-recognition of epitopes or through bystander activation mediated by the cytokine environment (28,47,48). Specific memory T cells could also be activated as a result of reactivating latent pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Specific memory T cells could also be activated as a result of reactivating latent pathogen. Although CMV may reactivate as a consequence of cytokine-driven differentiation of myeloid cells (20), reactivation is not necessary to activate CMV-specific T cells in acute EBV, HIV, or hepatitis B virus infection (28,48,49). Collectively, these studies suggest that the activation of pre-existing memory cells could be important for the course of a secondary infection and for T cell homeostasis (discussed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that bystander activation is prevalent during the early stages (<7 days) of influenza infection. Antigen non-specific bystander activation has been well documented in a number of viral infections [12,28], including influenza [29,30]. While others have observed bystander activation, little is known about the specific phenotype and/or function of these cells during infections.…”
Section: Phenotype Of Cd8 + T Cells After Primary Influenza Infectionmentioning
confidence: 99%
“…Other studies using tetramers have revealed much higher antigenspecific responses in certain viral models; up to 80% of CD8 + T cells in the spleen of lymphochoriomeningovirus (LCMV)-infected mice have been shown to be specific for 10 different LCMV-derived epitopes at the peak of primary infection [9][10][11]. Another study investigating newly HIV-infected humans showed activation of approximately 50% of the circulating T cells, only about 1% of which were HIVspecific [12]. During influenza infection, it has been observed that up to 70% of lung infiltrating CD8 + T cells showed signs of activation, whereas only 30% of those CD8 + T cells also stained positive for specific major histocompatibility complex (MHC) tetramers, given the current repertoire of known viral epitopes [13].…”
Section: Introductionmentioning
confidence: 99%